Determination of infiltration gallery yield using 2-dimensional analytic element method - Tongol, John Vincent G.
Infiltration galleries are perforated horizontal pipes used to extract groundwater in order to cater the water demand of a nearby community. In order to conduct proper water management in the area, the actual supply of water coming from the infiltration gallery is a priori. Using Analytic Element Method (AEM), the infiltration gallery yield is determined. AEM, which was developed by Otto D.L. Strack, is an approximate way of modeling acquifers which involves the idea of superposition of analytic elements that represents hydrogeological features of an area as opposed to numerical methods that involves discretization of the area into finite differences or elements. The infiltration gallery system being modeled is located underneath the Dacanlao River in Calaca, Batangas. The method is limited only to a single homogeneous aquifer. Also, the study was only limited to a two-dimensional application of the Analytic Element Method. The Visual AEM, a freeware, was used to model the infiltration gallery system. The model is composed of four analytic elements: (1) the underlying aquifer, (2) a river directly above the galleries, (3) the nearby sea, and (4) the four horizontal wells. The coordinates of specific points on each element were digitized through a mapping software, Google Earth. These points were plotted and the properties were inputted to the Visual AEM. The final extraction rates for each pipe are 4.69 MLD for the outer pipes while 4.19 MLD for the inner pipes. The total infiltration gallery yield was 17.75 MLD. The model was validated by getting the difference of the resulting infiltration gallery yield from the observed spot yield. The percent difference was -10.31%, indicating that the Analytic Element Method (AEM) underestimates the capacity of the yield. In comparison, the MODFLOW Model of the same groundwater system done by Macuha (2016) has +10.13% difference. The result of the proposed alternate method is comparable to that of the numerical method. Acquiring almost the same accuracy in the result, requiring very few input data, and having a very short period run time in the model execution, the use of the Analytic Element Method (AEM) in determining the yield of infiltration galleries must be further explored and tested.